Molecular detection of acute hepatopancreatic necrosis disease (AHPND) in Penaeus vannamei shrimps in Costa Rica - Nelson Peña-Navarro (2020)
Acute hepatopancreatic necrosis disease (AHPND) is a bacterial disease associated to severe mortality in farmed shrimps, and caused by Vibrio parahaemolyticus containing plasmid pVA-1 encoding pirA and pirB toxins. This study investigates the presence of Vibrio spp. carrying plasmid pVA-1 in post larvae and juveniles Penaeus vannamei from farms located in Costa Rica. Moreover, a possible corelation between Vibrio spp. presence, management parameters, and water quality was also investigated. Between 2017 and 2018, post larvae, the first water pumped into ponds, and juvenile shrimp (6 to 7 weeks after stocking) were collected from 15 farms located in the Gulf of Nicoya and the country's Central Pacific region. On the day when the juvenile shrimp were collected, a survey was applied to farmers to obtain information about management conditions, finally physicalchemical parameters of pond water were measured. Plasmidic pVA-1 pirA and pirB genes were detected in hepatopancreas of juvenile shrimp in 5 (33.3%) farms, while Vibrio spp. were found in 6 (40.0%) farms. Sequencing of pVA-1, pirA and pirB genes showed 99–100% similarity to pathogenic Vibrio parahemolyticus XN89 homologous genes identified in Vietnamese shrimps. Statistically significant differences were found in the water volume (p < .03), rate of water replacement (p < .04), and farms disease history (p < .05). A correlation between presence of Vibrio spp. and water quality was not established. The molecular diagnosis of Vibrio spp., the plasmid and the genes encoding toxins that are associated with AHPND are reported for the first time in Costa Rica. Further studies aimed to isolate AHPND-causing Vibrio spp. from ponds, to generate histopathological data, and to establish economic losses due to AHPND mortalities in Penaeus vannamei farms, are needed to clarify the role and pathogenic features of Vibrio spp. in AHPND.